Comparative analysis of life expectancy in South America, 1980 - 2010 - Restrepo Betancur, Luis Fernando; Rodríguez Espinosa, Holmes (Universidad y Salud, 2014)
Introduction: Life expectancy is a parameter of vital interest to design development strategies in a country in terms of education, health, transport, pension system, among others. This research aimed to make a comparison in terms of life expectancy among countries of South America and its relationship with the investment of gross domestic product on health. Materials and methods: A Multivariate analysis of variance (MANOVA) with canonical orthogonal contrast, exploratory descriptive analysis of one-dimensional type was used, based on the analysis of different databases from the World Health Organization, the Pan-American Health Organization and National Administrative Department of Statistics (DANE), according to sex and country factors. Results: A highly significant difference between countries (p<0.0001) with regard to life expectancy was found, observing a remarkable average increase in recent decades for both genders where Chile has the highest life expectancy and Bolivia the lowest one for South America. Conclusions: In general, life expectancy in South America has increased. No relation between life expectancy and public health investment as a percentage of GDP was detected.